A novel marine-derived anti-acute kidney injury agent targeting peroxiredoxin 1 and its nanodelivery strategy based on ADME optimization - Ping Yu; Tanwei Gu; Yueyang Rao; Weimin Liang; Xi Zhang; Huanguo Jiang; Jindi Lu; Jianglian She; Jianmin Guo; Wei Yang; Yonghong Liu; Yingfeng Tu; et al. (Elsevier, 2024)
Insufficient therapeutic strategies for acute kidney injury (AKI) necessitate precision therapy targeting its pathogenesis. This study reveals the new mechanism of the marine-derived anti-AKI agent, piericidin glycoside S14, targeting peroxiredoxin 1 (PRDX1). By binding to Cys83 of PRDX1 and augmenting its peroxidase activity, S14 alleviates kidney injury efficiently in Prdx1-overexpression (Prdx1-OE) mice. Besides, S14 also increases PRDX1 nuclear translocation and directly activates the Nrf2/HO-1/NQO1 pathway to inhibit ROS production. Due to the limited druggability of S14 with low bioavailability (2.6%) and poor renal distribution, a pH-sensitive kidney-targeting dodecanamine-chitosan nanoparticle system is constructed to load S14 for precise treatment of AKI. l-Serine conjugation to chitosan imparts specificity to kidney injury molecule-1 (Kim-1)-overexpressed cells. The developed S14-nanodrug exhibits higher therapeutic efficiency by improving the in vivo behavior of S14 significantly. By encapsulation with micelles, the AUC0‒t, half-life time, and renal distribution of S14 increase 2.5-, 1.8-, and 3.1-fold, respectively. The main factors contributing to the improved druggability of S14 nanodrugs include the lower metabolic elimination rate and UDP-glycosyltransferase (UGT)-mediated biotransformation. In summary, this study identifies a new therapeutic target for the marine-derived anti-AKI agent while enhancing its ADME properties and druggability through nanotechnology, thereby driving advancements in marine drug development for AKI.